The Effect of Subcutaneous Injection of Unfractionated and Low Molecular Weight Heparin on Thrombin Generation in Platelet Rich Plasma - A Study in Human Volunteers - Bendetowicz, A Vicky; Kai, Hu; Knebel, Richard; Caplain, H; Hemker, H Coenraad; Lindhout, Theo; Béguin, Suzette (Thrombosis and Haemostasis, 1994)
We administered a dose of unfractionated heparin (UFH) and two doses of a low molecular weight heparin (LMWH) to healthy volunteers by SC injection. The doses given were: a) UFH, 5000IU, which represents 8.7 mg of >5,400 MW active heparin (ACLM) and no <5,400 active heparin (BCLM), b) enoxaparin 40 mg (3.4 mg ACLM, 2.2 mg BCLM) and c) enoxaparin 1 mg/kg body weight (on the mean 75 mg, containing 6.4 mg ACLM and 4.1 mg BCLM). We determined the effect on thrombin generation in platelet rich plasma (PRP) between 1 and 8 h after injection. UFH administration caused only a 5-8% inhibition of the thrombin potential (i. e. the area under the thrombin generation curve). Significantly higher inhibition of the thrombin potential was seen after administration of both doses of enoxaparin. To wit 9-26% at the low dose and 29-46% at the high dose. UFH injection caused a prolongation of the lag-time before the thrombin burst. Only with the high dose of enoxaparin the lag-times were significantly more prolonged with enoxaparin than with UFH.Excess amounts of platelet factor 4 (PF4) were able to neutralize completely the anti-thrombin activity in normal plasma spiked with enoxaparin as well as in plasma samples obtained after SC enoxaparin injection. With a large excess of PF4 the anti-factor Xa activity could be inhibited to a maximum of 50%. This indicates that ACLM (above critical length material, MW >5400) is neutralized completely by PF4 whereas BCLM (below critical length material, MW <5400) is not. The anti-thrombin heparin-activity, hence the ACLM fraction of heparin, was shown to have disappeared from the serum of PRP samples. The BCLM fraction was found after coagulation of PRP in concentrations that were indistinguishable from those in the PPP.We conclude that in PRP the activity of the BCLM fraction of injected LMWH remains after platelet activation. The possible role of this activity in thrombin inhibition and in the antithrombotic action of low molecular weight heparins is discussed.